Why trust science in a trickster world of absolute contingency? The speculative force of mathematical abstraction - de Freitas, Elizabeth (Critical Studies in Teaching and Learning, 2023)
This paper explores a set of dilemmas associated with relational ontologies in which contingency factors prominently, raising the methodological question: how should we come to know, and trust our knowledge of the world? I explore distrust in science and the limits of empiricism under chaotic climatic regimes and argue that a pluralist ‘multiple earth’ must include mathematical fabulation and other kinds of speculative abstraction.